145 Conservation Grazing by Goats in Eastern Oak-hickory Forest: Browsing Behavior and Forage Selectivity. (8th October 2021) - Novais, Wanderson; Wenner, Benjamin; Block, Jeremy; Simon, Power; Elizabeth, Porteus; Davies, G Matt
Abstract: Oak-hickory (Quercus spp. and Carya spp.) recruitment and regeneration are negatively impacted by non-natives species. Goats can provide an initial control of non-native vegetation; however, browsing behavior and preference should be studied before their introduction in the forest. Our objective was to analyze goats' browsing behavior and preference in an eastern oak-hickory forest. We hypothesized that browsing behavior and preference are dependent on browse biomass composition and grazing duration. This study was conducted in Coshocton, Ohio, and contained two units with nine experimental plots each. Vegetation was surveyed during the summer of 2019 for biomass composition. Cluster analyses were performed using species identity and biomass. Vegetation nutritional analysis including fiber, protein, and sugar was completed. Two stocking rate densities were implemented: high (1, 019 goat×day×ha -1 ) and low (509×goat×day×ha -1 ). Goats browsed for four or two days for a total of 36 days. Continuous observation was implemented to determine browsing behavior. Forage selectivity was measured using Jacob's Selectivity Index (JSI). A linear mixed model was calculated using clusters, species, and/or grazing duration (fixed effect), experimental plots (random effect), and JSI (dependent variable). Spicebush (Lindera benzoin), multiflora rose (Rosa multiflora Thunb.), privet (Ligustrum spp.), and oriental bittersweet (Celastrus orbiculatus Thunb.) composed more than 70% of goats' diet. Species identity, including nutritional components and physical defense mechanisms, was the most important factor in browsing selectivity. Goats preferred spicebush and privet and avoided multiflora irrespective clusters (P 0.001). In the first two days of browsing, goats favored spicebush and privet, avoided multiflora, and had a neutral preference for bittersweet (P-value 0.001). In the last two days, privet was selected and other species had a neutral selection (P 0.001). Goats will target spicebush and privet and avoid multiflora; therefore, an extended browsing period is recommended. Future studies should evaluate the effect of chemical defense mechanisms on browsing.